ANALISIS RASIO PROFITABILITAS UNTUK MENILAI PERTUMBUHAN LABA PERUSAHAAN PADA PT INDAH KIAT PULP & PAPER TBK SERANG MILL - Abdul Rauf Chaerudin; Budi Kiswanto (Jurnal Bina Bangsa Ekonomika, 2020)
PT Indah Kiat Pulp & Paper Tbk Serang Mill is a manufacturing company engaged in the paper and pulp industry. To achieve the objectives of a company, the main thing is the company must be able to regulate its financial condition. A company cannot be said to be healthy only from its physical perspective, but from its financial performance element, because from that element it can be seen how well and healthy its financial condition is. This study aims to determine the amount of profits earned by the company each period based on financial statements during 2012-2016 seen from profitability ratios that include Profit Margin (Sales Profit Margin), Return On Investment (ROI), Return On Equity (ROE) and Earning per Share (EPS).